Heat and hospitalization risks among people with disabilities in South Korea - Jinah Park; Ayoung Kim; Ziyad Al-Aly; Kristi L. Ebi; Ho Kim; Whanhee Lee (Nature Communications)
Abstract Heat is known to have harmful impacts on health; however, little is known about its impact on people with disabilities. We evaluate the association between heat and hospitalization through the emergency department among people with and without disabilities. We adopt a case-crossover design using 16 years (2006–2021) of claims data from the Korean National Health Insurance Service Database. A total of 584,743 admissions are recorded among people with disabilities. The heat risk (odds ratio) is 1.10 (95% confidence interval: 1.08–1.13) in people with disabilities. The relative heat risk between people with and without disabilities is 1.33 (95% confidence interval: 1.29–1.37). Within the population with disabilities, individuals with brain lesion disorders, intellectual and mental disabilities, or living in areas with low-middle population density exhibit higher heat risks than the total people with disabilities. Here, we show evidence of different heat risks between people with and without disabilities.